PEMANFAATAN ASESMEN DIAGNOSTIK DAN MEDIA AJAR INTERAKTIF DALAM PEMBELAJARAN NORMA DI KELAS V SDN TEGALSARI 01 - Astrid Azzahra; Elisa Cristy Nugrahesi; Susilo Tri Widodo; Dhofi Ramadhan Nur (STKIP Subang, 2023)
In Permendikbudristek No. 56 of 2022, it sets standards for curriculum implementation in the context of learning recovery. The implementation of an independent curriculum allows teachers to create teaching tools that suit the learning needs, interests and competencies of each student. The purpose of this study is to identify student weaknesses through diagnostic assessment so that learning can be designed according to student competencies, as well as make it easier for students to understand the material with the use of interactive teaching media in Pancasila Education subjects in grade V SDN Tegalsari 01.